DiagnosTEA: a digital game as a tool for the diagnosis/therapy of Autism Spectrum Disorder - Barbosa, Bruna; Ribeiro, Marcos W.; Berretta, Luciana; Carvalho, Sergio (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2024: Anais do XXIII Simpósio Brasileiro de Jogos e Entretenimento Digital, 2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by criteria present in the domains of socio-communicative deficits and behavior. Considered challenging to diagnose and consequently lacking appropriate therapeutic applications, autism presents significant challenges for the scientific community. This study aims to design and develop a digital game as an auxiliary solution for diagnosing and treating ASD. As a methodology, a Systematic Literature Review was conducted to understand, adapt, and qualify specific concepts and methods related to ASD that can be used as particular features of a digital game built using the Unity Game Engine, with a suitable game genre and theme, along with scales and parameters that allow adaptation to the principles associated with the disorder. As a result of this research, a digital game for ASD named DiagnosTEA was created and tested to validate the entire process.